A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages Grouped practice means practice by a group of doctors working in co-operation. Separate practice means practice by a doctor working on his own account — broadly similar to practice under the present National Health Insurance scheme, but with important changes. (c) Grouped practice will be conducted normally, though not exclusively, in specially equipped and publicly provided Health Centres. In England and Wales, the Centres will be provided and maintained by county and county borough councils — in Scotland, by the Secretary of State with power to delegate to a local authority. (d) General practice in the National Health Service will be in the main organised centrally under the responsible Health Ministers. All the main terms and conditions of the doctor's participation will be centrally settled, and much of the day-to-day administration will be the function of Central Medical Boards — one for England and Wales and one for Scotland — largely professional in composition, and acting under the general direction of the Health Ministers. (e) The main duties of each Board will be :— (i) to act as the "employer" of the doctors engaged in the public service. Thus, the Board will be the body with whom every doctor will enter into contract. In the case of practice in Health Centres in England and Wales, however, there will be a three-party contract between the Board, the local authority and the doctor. (ii) To ensure a proper distribution of doctors throughout the country. For this purpose the Board will have power to prevent the taking over of an existing public practice or the setting up of a new public practice in an area which is already "over-doctored." (f) It is not proposed that there should be a universal salaried system for doctors in the new service. Doctors engaged in Health Centres will be remunerated by salary or the equivalent ; doctors in separate practice normally by capitation fee. In some cases — e.g. grouped pracdce not based on a Health Centre — remuneration by salary or the equivalent could be arranged if the doctors concerned so desired. Rates of remuneration will be discussed with the medical profession. (g) It is not proposed to prohibit doctors in public practice from engaging also in private practice for any patients who still want this. Where a doctor undertakes private in addition to public practice, the number of patients he is permitted to take under the National Service — and consequently his remuneration — will be adjusted. (h) Young doctors entering individual practice in the public service 30 36/H24/41